Digital Virality of Incest Fantasy: Media Law Challenges and Family Law Implication - Nabilah Falah; Mujjadiddah Aslamiyyah (Universitas Negeri Semarang, 2025)
This study examines the virality of the “Incest Fantasy” group on social media as a form of sexual deviance that is explicitly prohibited in both Islamic teachings and Indonesia’s positive law. The objective of this research is to analyze the case through the lens of media law and Islamic family law, highlighting the role of digital technology in normalizing deviant behavior and exposing the weakness of child protection systems. This research employs a normative qualitative approach with descriptive analysis, using secondary data and an interdisciplinary framework. The findings reveal that such deviant behavior constitutes a serious violation of family honor (ḥurmat al-usrah), the principle of lineage protection (ḥifẓ al-nasl), and moral values upheld by Indonesian legislation, such as the Child Protection Act and the Electronic Information and Transactions Law (ITE Law). Moreover, this case demonstrates the lack of effective oversight by digital platforms regarding morally harmful content. Therefore, an integrated legal approach is urgently needed, complemented by educational, religious, and preventive strategies to protect children from the destructive influence of digital content and to restore the role of Islamic values in preserving family integrity.